2015
DOI: 10.1089/sur.2014.134
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Surgical Site Infection after Acetabular Fracture Surgery

Abstract: To reduce the incidence of SSI in patients with acetabular fractures, special attention should be paid to the obese patients, Morel-Lavallée lesion, and concomitant abdominal trauma. Keeping the operative time short also reduces the risk of SSI. It is important to perform surgical intervention immediately after the infection occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
0
16
1
1
Order By: Relevance
“…We found many factors associated with SSI after acetabular fracture surgery such as the prolonged operative time 9) , high BMI 10) , prolonged ICU stay 11) , high rate of PRBC 12) , and associated abdominal and genitourinary trauma 13) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found many factors associated with SSI after acetabular fracture surgery such as the prolonged operative time 9) , high BMI 10) , prolonged ICU stay 11) , high rate of PRBC 12) , and associated abdominal and genitourinary trauma 13) .…”
Section: Discussionmentioning
confidence: 96%
“…In our study associated injury such as abdominal injury (splenic injury) and genitourinary trauma (bladder injury) also had positive influence on SSI. Li et al 13) reported in his study that abdominal trauma and urinary tract trauma are commonly associated with SSI following acetabular fracture fixation. Hence, special attention must be made while treating associated injuries to reduce the incidence of SSI.…”
Section: Discussionmentioning
confidence: 98%
“…They are caused by bacteria that invade through the incisions during surgery and may develop near the skin surface around an incision or deep in the surgical wound, thus representing serious complications [18]. Risk factors for surgical site infections include extended preoperative hospitalization, massive intraoperative blood loss, larger amount of packed red blood cell unit transfused, and prolonged surgery time [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…First, it is a relatively easy anatomical dissection involving fewer anatomical layers than Stoppa ( Figure 10 ). The duration of surgical exposure is another factor related to infection [ 3 , 25 ]. We think this easy and time-saving approach can play a role in preventing infection by shortening this procedure time.…”
Section: Discussionmentioning
confidence: 99%